Strong Cr–O Hybridization Prevents Active Cu(II) from Cathodic Reconstruction for Alkaline Hydrogen Evolution Catalysis. Issue 12 (25th September 2022) - Fang, Yanyan; Wei, Cong; Niu, Shuwen; Liu, Bo; Yin, Xuanwei; Bian, Zenan; Tang, Chongyang; Wang, Gongming
Abstract : The fully filled d 10 orbital structure of metallic Cu is inert for alkaline hydrogen evolution reaction (HER), whereas its oxidized state, CuO with platinum (Pt)‐like d 9 configuration has been predicted to benefit catalysis. However, the weak Cu(II)–O hybridization undergoes thermodynamically favorable cathodic reconstruction to metallic state during HER process. Herein, Cu(II) is successfully stabilized via introducing strong Cr–O hybridization and its potential for HER is unfolded. The Cr‐modified Cu(II) oxide surface delivers an overpotential of 247 mV at 100 mA cm −2, which is substantially better than the pristine metallic Cu (549 mV). Refined structural analysis confirms the existence of abundant Cu(II) with Cr incorporation. Theoretical calculations unravel the strong covalent Cr–O interaction that confines lattice O nearby Cu sites, leaving Cu(II) for the catalysis. The concepts of employing strong hybridization to secure active yet unstable catalytic sites provide a new vision for catalyst design. Abstract : Thermodynamically favorable cathodic reconstruction of active Cu(II) is suppressed via introducing strong Cr–O hybridization. The strong covalent Cr–O interaction confines structural O atoms and further stabilized the Cu(II) with platinum (Pt)‐like d 9 orbital configuration. The preserved Cu(II) active center exhibits great benefit for alkaline hydrogen evolution reaction catalysis.